SOUTH CAUCASIAN CONFLICTS: ECOVERY BEGINS WHEN THE DISEASE IS RECOGNIZED AND THERE IS A DESIRE TO CURE IT - MAYOROV, Mikhail (CENTRAL ASIA AND THE CAUCASUS, 2004)
At the end of 2003, the Southern Caucasus experienced several political earthquakes. New heads of state came to power in Azerbaijan and Georgia, thus compelling politicians to ponder the future of the Georgian Abkhazian, Karabakh and Georgian-Ossetian conflicts in a new light. The Georgian events caused the greatest waves. Late in November 2003, the heads of Abkhazia, Adzharia, and South Ossetia came to Moscow immediately after Shevardnadze’s resignation. Tbilisi betrayed its displeasure by saying that had not certain serious forces in Russia supported the separatists, the conflicts in Abkhazia and South Ossetia would have been settled long ago. Regrettably, this was not the first time such statements were made. However, the Moscow consultations organized on the initiative of the heads of the above-mentioned republics were completely justified. Russian Foreign Minister Igor Ivanov remarked: “No one should suspect a plot or moves behind the scenes. Russia has never been engaged in such activities and is not engaged in them now.”1 The heads of the Georgian republics came to Moscow to express their attitude toward the events, as well as their concern over a possible spread of the Tbilisi crisis to their regions. Everybody knows that both Sukhumi and Tskhinvali were following the shift at the top in Tbilisi with a great deal of anxiety; they were especially troubled by the statements of the new leaders that the